1997
DOI: 10.1007/pl00008702
|View full text |Cite
|
Sign up to set email alerts
|

A 25-kb deletion in the 5′ region of the cytochrome b558 heavy chain gene (CYBB) in a patient with X-linked chronic granulomatous disease

Abstract: We performed molecular genetic analyses of the family of a boy suffering from chronic granulomatous disease (CGD) after immunocytochemically confirming him and his mother to be an X-linked CGD patient and a mosaic carrier, respectively. Southern blot hybridization using cDNA for the cytochrome b 558 heavy chain gene (CYBB) as a probe showed that the patient had a deletion in the 5′ region of the CYBB and his phenotypically normal mother was heterozygous for this deletion. Polymerase chain reaction analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…Altered bands (arrow) of StuI-digested DNAs in the patient and his mother (P and M, respectively in Fig. 4A) were consistent with the findings reported previously (Faizunnessa et al, 1997). The patient's grandmother (G) and aunt (A) were genetically normal, as were his brother (B) and an unrelated normal person (C) (Fig.…”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…Altered bands (arrow) of StuI-digested DNAs in the patient and his mother (P and M, respectively in Fig. 4A) were consistent with the findings reported previously (Faizunnessa et al, 1997). The patient's grandmother (G) and aunt (A) were genetically normal, as were his brother (B) and an unrelated normal person (C) (Fig.…”
Section: Figsupporting
confidence: 90%
“…Our previous study showed that this CGD patient has the 25-kb deletion upstream of exon 7 or neighboring introns of CYBB (Faizunnessa et al, 1997). To determine breakpoints in his CYBB, the patient's genomic DNA library containing 10-to 15-kb Sau3AI fragments was screened with the labeled 5Ј half of the CYBB cDNA as a probe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have carried out a statistical analysis of 229 CGD patients from 195 families in Japan and the mutation analysis of an additional 28 independent gp91-phox deficient and five independent p22-phox deficient patients to those published previously from Japan (Ariga et al 1998;Azuma et al 1995;Faizunnessa et al 1997;Kaneda et al 1999;Okubo et al 1992;Suzuki et al 1998;Tsuda et al 1998;Yoshida et al 1998). Altogether, mutation analysis of a total of 48 out of 109 cases identified as gp91-phox deficiency (44%) and a total of five out of 16 cases of p22-phox deficiency in Japan (31%) has been accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation analysis of the other 20 Japanese cases has been reported (Ariga et al 1998;Azuma et al 1995;Faizunnessa et al 1997;Kaneda et al 1999;Okubo et al 1992;Suzuki et al 1998;Tsuda et al 1998;Yoshida et al 1998).…”
Section: Statistical Analysis Of Cgd Patients In Japanmentioning
confidence: 92%